Knowledge, attitude, and practice on antibiotic use in DKI Jakarta during COVID-19 pandemic - Andini, Dheanita Nissrina; Gayatri, Anggi; Jonlean, Reganedgary (Faculty of Medicine, Public Health, and Nursing Universitas Gadjah Mada and Indonesian Pharmacologist Association or Ikatan Farmakologi Indonesia (IKAFARI), 2025)
Insufficient knowledge of antibiotic use among the general public could lead to antibiotic resistance. As the COVID-19 pandemic might encourage antibiotic self-medication, a study about recent knowledge, attitude, and practice (KAP) levels on antibiotic use during the COVID-19 pandemic needs to be carried out, including its possible associated factors. It is a cross-sectional study with 420 subjects living in DKI Jakarta and aged 18 or above. A validated KAPAQ questionnaire was used. Chi-square analysis was used to analyze the correlation between KAP levels and its possible associated factors. Most subjects’ score of KAP in antibiotic use were considered high. A statistically significant correlation between knowledge and attitude (p<0.001), knowledge and practice (p<0.001), and between attitude and practice (p<0.001) was found. A statistically significant correlation between gender and occupation fields with KAP (p<0.05), education level with knowledge (p<0.05), and history of self-medication with attitude and practice (p<0.05) were found. Age, marital status, and history of COVID-19 do not show any statistically significant correlation with KAP levels. In conclusion, most subjects have a high score of KAP in antibiotic use. All three variables also show significant correlations between each other while the sociodemographic factors that correlate significantly with KAP levels are gender, occupation field, education level, and history of self-medication with antibiotics.